Public perception towards government expenditure on prisoners : Case study in Kota Bharu, Kelantan / Nurul Izzatie Md Adnan - Md Adnan, Nurul Izzatie (2012)
The purpose of this study is to examine the public perception towards the Government expenditure on prisoners. This case study will be done in Kota Bharu, Kelantan. In Kelantan, there is a Prison in Pengkalan Chepa that controls all the prisoners that has been convicted. This study used the development of a multiple linear regression analysis model to identify the significant influence of public perception towards the Government expenditure on prisoners. There are three independent variables that are used which are crime rates, prison program, and medical facilities. Questionnaire will be used in order to obtain data. There are total of five sections in the questionnaire. First section is based on the demographic profiles and second section is based on the dependent variables which is the perception on the government expenditure. Third section is about the first independent variable which is the crime rate. Fourth and fifth section is also about the independent variables where the fourth section is on prison program and fifth section is on medical facilities. This research will use frequency analysis, reliability analysis, descriptive analysis and regression analysis to obtain the result of the finding. Result showed that there are two independent variables that have significant influence which are crime rates and medical facilities, and only one independent variable which is prison program that does not have significant influence on the public perception towards government expenditure on prisoners in Kelantan